Political identity and social change : the remaking of the South African social order - Frueh, Jamie, 1966- (SUNY series in global politics., 2003)
"Political Identity and Social Change builds upon the constructivist theory of political identity to explore the social changes that accompanied the end of apartheid in South Africa. To gain a better understanding of how structures of identity changed along with the rest of South Africa's institutions, Frueh analyzes three social and political conflicts: the Soweto uprisings of 1976, the reformist constitutional debates of 1983-1984, and post-apartheid crime. Analyzing these conflicts demonstrates how identity labels function as structures of social discourse, how social activity is organized through these structures, and how both the labels and their power have changed during the course of South Africa's transition. In this way, the book contributes not only to the study of South African society, but also provides lessons about the relationship between identity and social change."--Jacket